2020
DOI: 10.1155/2020/8159342
|View full text |Cite
|
Sign up to set email alerts
|

PBMCs to Stress-Associated miR-18a-5p and miR-22-3p Ratios as New Indicators of Metabolic Syndrome

Abstract: Purpose. Metabolic syndrome (MetS) is associated with chronic stress. miR-18a-5p and miR-22-3p are two miRNAs which can target the glucocorticoid receptor. This study looked at the changes in metabolic parameters and the predictive value of the peripheral blood mononuclear cells (PBMCs) to stress-associated miRNA ratios as new indicators in subjects with and without MetS in southern China. Patients and Methods. There were 81 participants (39 with MetS and 42 without MetS) in this cross-sectional study. The pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“… 14 , 15 miR-18a-5p can target the glucocorticoid receptor, which is involved in the regulation of inflammatory response and related physiological events. 29 In the current study, the gain and loss function experiments revealed that upregulation of miR-18a-5p aggravated CSE-induced cell apoptosis and inflammatory cytokines release. Moreover, miR-18a-5p overexpression reversed the influence of CASC2 on cell apoptosis and inflammation in 16HBE cells.…”
Section: Discussionmentioning
confidence: 51%
“… 14 , 15 miR-18a-5p can target the glucocorticoid receptor, which is involved in the regulation of inflammatory response and related physiological events. 29 In the current study, the gain and loss function experiments revealed that upregulation of miR-18a-5p aggravated CSE-induced cell apoptosis and inflammatory cytokines release. Moreover, miR-18a-5p overexpression reversed the influence of CASC2 on cell apoptosis and inflammation in 16HBE cells.…”
Section: Discussionmentioning
confidence: 51%
“…The detailed characteristics of the selected studies are shown in Table S2, Supplemental Digital Content, http://links.lww.com/MD/L813. Thirty-seven studies [5,11–46] defined MetS according to the third report of the National Cholesterol Education Program-Adult Treatment Panel. [47] Fifteen studies [6,48–61] assessed metabolic syndrome using the International Diabetes Federation criteria.…”
Section: Resultsmentioning
confidence: 99%
“…In proliferative diabetic retinopathy and diabetic cardiac fibrosis, the abnormal change of miR-18a-5p expression was associated with the development of complications of diabetes [9,11]. In patients with metabolic syndrome, the miR-18a-5p was lessened relative to control subjects, and its levels correlate with the expression of IL-6 [14]. In this present investigation, the lowly expressed miR-18a-5p restricted the depressed infarct size, Bederson score, and Longa score led by UCA1 loss, which documented that the beneficial impacts of diminished UCA1 on CI/R injury were regulated by miR-18a-5p.…”
Section: Discussion/conclusionmentioning
confidence: 99%